Sistem Pengambilan Keputusan Penentuan Kualitas Biji Kopi Ekspor Menggunakan Metode TOPSIS dan VIKOR (Studi Kasus : Biji Kopi Ekspor Pada Tiap Koperasi) - Angga Pratama; Rizki Mela Kurnia; Veri Ilhadi (STMIK Sinar Nusantara, 2023)
Coffee, which has grown to be one of the most popular traditional plantation crops, contributes significantly to the economics of a coffee-producing region. Central Aceh, Bener Meriah, and Gayo Highlands are three of Indonesia's largest coffee-producing districts. A number of standards must be met in order for coffee beans to be regarded high grade and fall into the category of quality beans. TOPSIS and VIKOR methods were utilized in this research to develop a decision support system for assessing the quality of exporting beans. This system generates a rating as an output based on input values and weights, with weight values that can be adjusted by the chosen criteria. The purpose of this research is to develop software for grading coffee beans based on user input such as bean flaws, water volume, bean size, bean color, and aroma. Moreover, after two methods had been evaluated, TOPSIS method with the results of Gayo Permata cooperative with Grade 1 Arabica Gayo Coffee was recognized as the most effective method. Based on the results of KBQ Baburrayan cooperative using Arabica Gayo Coffee, TOPSIS is closer to the ideal solution than the VIKOR approach.